Roles and Responsibilities of Institution Legal Assistance In The Process of Handling the Case of Crime(Case Study: Criminal Investigation in Directorate of Central Java Regional Police) - Yogi Setiyo Pamuji; Jawade Hafidz (Jurnal Daulat Hukum, 2019)
Legal aid is a legal service which aims to provide a defense against human rights. The method used in this study is juridical empirical sociological law research that examines the applicable law and what happens in reality in society. In this study, the law conceived as an empirical phenomenon that can be observed in real life. The theory used in this research is the theory of the rule of law, theory principle of legal certainty, fairness and legal benefit.The study concluded that: 1) The role and responsibilities of legal aid refers to Article 1, Section 7, Article 8, Article 9, Article 10, Article 11, Article 13, Article 15, Article 20, Article 21 of Act Number 16 2011. 2) the obstacles faced by Legal aid Society in carrying out their roles and responsibilities are: a) the lack of continued patently victims and perpetrators of crime, b) lack of communication between legal aid providers with the investigator, c) attitude of investigators who sometimes covered with their view that a legal aid provider will impede the process of investigation, d) existence of different legal interpretations between Advocacy Legal aid to investigators about the conclusions and investigations. 3) Solutions related constraints faced by Legal Aid Society in carrying out their roles and responsibilities are: a) Government should give special warning to do the legal laid as Act Number 16 of 2011, b) Improve coordination between Police and Legal Laid Board connected with the Legal Laid, c) Followed investigator in socialization on law about legal laid.Keywords: Legal Aid; Legal Aid Board; Crime.